Heaney's Hauntings: Archaeology, Poetry and the 'Gendered Bog'. Issue 1 (3rd July 2019) - Everett, Rosie; Gearey, Benjamin
ABSTRACT: In this paper we discuss the entangled relationship between literary creation, archaeology and representations of gender in the poetry of Seamus Heaney, in particular the 'bog poems' The Tollund Man and Bogland . We trace the early formative connections between the poet, peatlands and 'bog body' research, in which both literary critical and archaeological scholars have analysed themes including 'the bog as archive', theory and practice of archaeology and the process of poetic creation and imagining in Heaney's writings. We discuss archaeological perspectives on Heaney's poetry, and outline literary critique that has problematised the representation of gender in the 'bog poems'. Finally, we consider the poem Bogland and read this through the lens of Irish peatland archaeology, in particular its destruction by industrial peat extraction. To conclude, we reflect how Heaney's poetry as a form of archaeological knowledge and narratives must continue to be subject to 'excavation', contextual readings and critique.